Faktor-Faktor yang Mempengaruhi Pengembangan Karir, Disiplin Kerja, dan Lingkungan Kerja terhadap Kinerja Pegawai pada PT XYZ - I Nyoman Bagus; I Gede Aryana Mahayasa; Luh Nik Oktarini (Media Bisnis, 2025)
Factors including professional advancement opportunities, work disciplline, and a positive work environmen may have on impact on how well employees perform. A person's capacity to get their ideal job is enhanced via career development. The capacity to consistently and methodically complete tasks is what mean when we tallk about work discipliine. When workers go about their daily tasks, the workplace plays a significant role. This reserch ams to determin the impact of carier developmen, work disciplline, and enviroment an employe performancee, both individually and in combination. At PT XYZ, the research was caried out. The 38 employees were all included in the total for the pourpose of this studi. Saturation sampling was used to decide that a total of 38 persons would be include in the samplle. Data wass colected via interviews, written records, and questionnaires using Likert scales. This research made use of mulltiple linear regresion. The evidence shows that carer advancement opportunities, work disciplin, and a pleasant work enviroment have a favorable and substantial efect on employe performanc. When professional development possibilities, work disciplline, and the worrk environment are all taken into account simultaneously, they have a possitiv and substantial influence on employse performnce. It is recomended that career development options be expanded upon, the important of work disciplline be highlighted, and a good work environmen be maintained in order to promote continual improvement in employe performan.